Molecular identification of shark fins in Malaysian Borneo’s local markets - BADRUL MUNIR MD-ZAIN; SITI NUR AZMINA ABID-KAMAL; NOR RAHMAN AIFAT; MUHAMMAD ABU BAKAR ABDUL-LATIFF; ABU MOHD- HASHIM; AHMAD AMPENG; SALMAH YAAKOP; ABDULLAH SAMAT (Society for Indonesian Biodiversity, 2018)
Md-Zain BM, Abid-Kamal SNA, Aifat NR, Abdul-Latiff MAB, Mohd-Hashim A, Ampeng A, Yaakop S, Samat A. 2018. Molecular identification of shark fins in Malaysian Borneo’s local markets. Biodiversitas 19: 1035-1043. A molecular study was carried out to investigate the potential of the cytochrome c oxidase subunit I (COI) gene as a molecular marker for the genetic identification of shark fin samples that have gone through various preservation processes. A total number of 17 shark fin samples were collected from local markets in Sabah and Sarawak (Malaysian Borneo). The DNA sequences of the 17 samples were amplified by using polymerase chain reaction. The results from the analysis showed that, in the 17 sequences, there were 16 haplotypes present, with 244 sites from 688 bp of the sequences. For phylogeny analysis, tree topologies were reconstructed using the neighbor-joining (NJ) and maximum parsimony (MP) methods. DNA barcoding technique successfully identifies shark fins collected in local markets in Malaysian Borneo at species level employed during this study. Phylogenetic analysis showed that there were four clades that distinguish the four different orders present in the sample species. These clades had bootstrap values higher than 80. In addition, results indicated that 88.2% of the individuals are listed as endangered (Lamiopsis tephrodes, Sphyrna mokarran, and Sphyrna lewini), vulnerable (Alopias pelagicus and Rhynchobatus australiae), and near threatened (Carcharhinus limbatus, Chiloscyllium griseum, Carcharhinus sorrah, and Carcharhinus brevipinna), in the International Union for Conservation of Nature (IUCN) Red Data List.